1992
DOI: 10.1111/j.1365-2559.1992.tb01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological prognostic factors in breast cancer. II. Histological type. Relationship with survival in a large study with long‐term follow‐up

Abstract: Pathological prognostic factors in breast cancer. 11. Histological type. Relationship with survival in a large study with long-term follow-upThe histological tumour type determined by current criteria has been investigated in a consecutive series of 162 1 women with primary operable breast carcinoma, presenting between 1973 and 1987. All women underwent definitive surgery with node biopsy and none received adjuvant systemic therapy. Special types, tubular, invasive cribriform and mucinous, with a very favourab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
0
14

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(178 citation statements)
references
References 36 publications
7
157
0
14
Order By: Relevance
“…Patient's clinical history and tumour characteristics including patients' age, menopausal status, bilaterality, family history, type and number of primary operation and axillary lymph node surgery, primary tumour size, histologic tumour type [6], histologic grade [33], lymph node (LN) status, vascular invasion (VI), NPI and oestrogen receptor (ER) status were obtained from the database. Survival data including survival time, disease free interval, and development of distant metastasis (DM), local and regional recurrence was maintained on a prospective basis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient's clinical history and tumour characteristics including patients' age, menopausal status, bilaterality, family history, type and number of primary operation and axillary lymph node surgery, primary tumour size, histologic tumour type [6], histologic grade [33], lymph node (LN) status, vascular invasion (VI), NPI and oestrogen receptor (ER) status were obtained from the database. Survival data including survival time, disease free interval, and development of distant metastasis (DM), local and regional recurrence was maintained on a prospective basis.…”
Section: Methodsmentioning
confidence: 99%
“…Invasive ductal (IDC) and invasive lobular (ILC) breast carcinomas are the most common types of breast cancer, accounting for 72-80% and 5-15% of invasive breast cancer respectively [1][2][3][4], while tumours with mixed histologic types (mixed ductal and lobular) are less common, accounting for 3-5% [5][6][7]. Several studies have reported that whereas the incidence of IDC has remained stable, the incidence of ILC and mixed ductal and lobular tumours are increasing particularly among postmenopausal women [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include histologic grade [35], histologic tumour type [36], vascular invasion (VI) [37], primary tumour size, and lymph node (LN) stage, and Nottingham prognostic index (NPI) [38] which were routinely assessed and recorded in the database as well as patients' information such as age, family history, and menopausal status. The clinicopathological characteristics of the series are presented in Table 1.…”
Section: Study Populationmentioning
confidence: 99%
“…All patients had been assessed in a standardised manner for clinical history and tumour characteristics including age, menopause status, tumour type [29], histological grade [30], tumour size, tumour recurrence, presence of distance metastasis, lymph node status, vascular invasion and Nottingham Prognostic Index (NPI) [31]. Data relating to survival was collated in a prospective manner including breast cancer specific survival (BCSS), defined as the interval (in months) from the date of the primary treatment to the time of death due to breast cancer, and disease free interval (DFI), defined as the interval (in months) from the …”
Section: Patient Samplesmentioning
confidence: 99%